Sural nerve pathology in TFG‐associated motor neuron disease with sensory neuropathy. Issue 3 (8th April 2019) - Li, Jia; Meng, Lingchao; Wu, Rui; Xie, Zhiying; Gang, Qiang; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun
Abstract : The tropomyosin‐receptor kinase fused gene ( TFG ) functions in vesicles formation and egress at the endoplasmic reticulum (ER). A heterozygous missense mutation c.854C > T (p.Pro285Leu) within TFG has been reported as causative for hereditary motor and sensory neuropathy with proximal predominance. Here, we describe two unrelated Chinese pedigrees with 13 affected members harboring the same variant. The clinical, electrophysiological and pathological findings are consistent with motor neuron disease with sensory neuropathy. The main symptoms were painful muscle cramps, slowly progressive proximal predominant weakness, muscle atrophy, fasciculation and distal sensory disturbance. Electromyography revealed widespread denervation and reinnervation. Sural nerve biopsy revealed severe loss of myelinated fibers. Electron microscopy revealed aggregation of ER with enlarged lumen and small vesicles in the remaining myelinated and unmyelinated axons. The mitochondria are smaller in Schwann cells and axons. Some unmyelinated axons showed disappearance of neurofilament and microtubular structures. This is the first report of c.854C > T mutation within TFG in Chinese population. Our findings not only extend the geographical and phenotypic spectrum of TFG‐ related neurological disorders, but also confirm the abnormalities of ER and mitochondria in sural nerves.